Retrospective study of clinico-pathological features of ovarian tumors - Vedpathak, Sachin G.; Nayak, Vaishali R. Korde (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian masses are a frequent clinical diagnosis in general Gynecology. The aim of the present study was to assess risk factors, clinical features, CA 125 levels, histopathological diagnosis of the patients of all ovarian tumors that underwent surgical management between August 2013 to August 2017. Methods: This was the retrospective study conducted in the department of Obstetrics and Gynecology in MIMER Medical College. We studied 50 patients those who underwent surgical management. Most of the patients 56% were in the reproductive age group, 28% patients were in the perimenopausal age group, 14% were in the postmenopausal age group. 82% patients were parous. Results: Pain abdomen was most common symptom in 50% patients. Bilaterality of the tumor was common in malignant tumors. CA 125 was found to be increased more in malignant tumors. Most common co morbid condition was hypertension found in 12% patients. Most common ovarian tumor found was serous cystadenoma 34% and most common malignant tumors were serous cystadenoma carcinoma 16%. Conclusions: Out of all operated patients 11 (22%) were malignant, 37 (74%) were benign and 2 (%) were borderline tumors. Out of all malignant tumors 8 (72%) were serous cysadenocarcinoma. It is difficult to always differentiate between malignant and benign tumors clinically. Analysis of risk factors and protective factors, thorough abdomino-pelvicbimanual examination, certain features on radiological imaging, presence of ascites and bilaterality, CA125 levels, helps increasing the accuracy of the diagnosis.